Genome Sequence of Rhodococcus erythropolis Strain CCM2595, a Phenol Derivative-Degrading Bacterium - Strnad, Hynek; Patek, Miroslav; Fousek, Jan; Szokol, Juraj; Ulbrich, Pavel; Nesvera, Jan; Paces, Vaclav; Vlcek, Cestmir (Genome announcements, 2014)
We announce the completion of the genome sequence of a phenol derivative-degrading bacterium, Rhodococcus erythropolis strain CCM2595. This bacterium is interesting in the context of bioremediation for its capability to degrade phenol, catechol, resorcinol, hydroxybenzoate, hydroquinone, p-chlorophenol, p-nitrophenol, pyrimidines, and sterols.